OER electrocatalyst and preparation method thereof

By forming Fe3S4/Ni(OH)2/NF catalyst under hydrothermal conditions and performing high-temperature sulfurization treatment, the problem of low cycle stability of non-noble metal electrocatalysts in alkaline electrolytes is solved, and the OER catalytic activity and performance are significantly improved. stability.

CN119352090AActive Publication Date: 2025-01-24INNER MONGOLIA UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411552608.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-24
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing non-precious metal electrocatalysts have low cycling stability in alkaline electrolytes, especially under high current density conditions.

Method used

Using reconstruction project and heterogeneous interface project, by reacting iron salt, nickel salt, nitrogen sources, and foam nickel -based reactions to form Fe3S4/NI (OH) 2/NF catalysts, it is formed. Sulfurization.

Benefits of technology

In an alkaline environment, the OER catalytic activity is significantly improved. In the 1.0M KOH OER reaction, the current density is 50mA CM-2, and the working potential is only 191mV; when the current density is 100mA CM-2, the working potential is 208mv And maintain stability of more than 100h under large current density conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352090A_ABST
    Figure CN119352090A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrocatalytic materials, in particular to an OER electrocatalyst and a preparation method thereof.The preparation method comprises the steps that ferric salt, nickel salt, a nitrogen source and a foamed nickel substrate are added into water, and a mixed solution is obtained; reacting the mixed solution under a preset temperature condition to obtain a precursor; the precursor is subjected to vulcanization treatment, and the OER electrocatalyst is obtained. According to the preparation method disclosed by the invention, the nanoflower-shaped precursor formed in the hydrothermal process still well retains the morphological characteristics of the nanoflowers in the high-temperature vulcanization process, so that enough active sites are fully exposed. The heterogeneous interface (Fe3S4 / Ni (OH) 2) in the electrocatalyst has a synergistic effect, so that the surface charge distribution of the catalyst is improved, the electron transfer rate is accelerated, and the OER catalytic activity is effectively improved. In a stability test under high current density, the Fe3S4 / Ni (OH) 2 / NF catalyst also shows excellent long-term stability, and when the current density is 100 mA cm <-2 >, the Fe3S4 / Ni (OH) 2 / NF catalyst can stably work for 100 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalytic materials, and in particular to an OER electrocatalyst and a preparation method thereof. Background Art

[0002] Hydrogen energy (H2, renewable clean energy) has the advantages of abundant sources, high energy density, zero emissions and storability, making it the most feasible energy source to replace fossil fuels. Currently, hydrogen production by water electrolysis has become one of the most ideal and feasible methods to provide hydrogen energy. Its reactions include hydrogen evolution reaction (HER, cathode reaction) and oxygen evolution reaction (OER, anode reaction). However, OER (oxygen evolution reaction) is the key half-reaction of electrocatalytic water decomposition, and its multi-electron transfer and slow kinetic process limit the energy utilization efficiency.

[0003] Among various non-precious metal electrocatalysts, nickel-iron-based nanomaterials have attracted extensive attention due to their cost-effectiveness, natural abundance, and favorable electronic configuration. To date, researchers have developed numerous highly efficient electrocatalysts that reduce the overpotential of OER, such as oxides, selenides, sulfides, phosphides, carbides, nitrides, metal alloys, (hydroxy) oxides, etc. of transition metals (Ni, Fe, Co, etc.). However, among the existing various non-precious metal electrocatalysts, there is a problem of low cycling stability in alkaline electrolytes, especially under high current density conditions.

[0004] Therefore, the prior art needs to be further improved and enhanced. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides an OER electrocatalyst and a preparation method thereof, aiming to solve the problem that the existing non-precious metal electrocatalysts have low cyclic stability in alkaline electrolytes.

[0006] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0007] In a first aspect, a method for preparing an OER electrocatalyst comprises:

[0008] Adding iron salt, nickel salt, nitrogen source and nickel foam substrate into water to obtain a mixed solution;

[0009] The mixed solution is reacted under a preset temperature condition to obtain a precursor;

[0010] Placing the precursor in a reaction container, and placing sulfur powder on one side of the precursor;

[0011] The reaction container is placed in a baking device and heated in an inert atmosphere to obtain the OER electrocatalyst; wherein the heating rate is 2-4°C min-1 ; Heating temperature is 300-400℃;

[0012] The molar ratio of the iron salt to the nickel salt is 1:5.

[0013] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0014] As a preferred technical solution, the preparation method of the OER electrocatalyst is described, wherein the iron salt is ferric nitrate nonahydrate or ferric sulfate heptahydrate; the nickel salt is nickel chloride or nickel nitrate hexahydrate; and the nitrogen source is selected from one or more of urea, ammonium fluoride, ammonium sulfate and ammonium nitrate.

[0015] As a preferred technical solution, the method for preparing the OER electrocatalyst, wherein the reaction is carried out under preset temperature conditions, wherein the preset temperature is 100-140°C and the reaction time is 2-10h.

[0016] In a second aspect, an OER electrocatalyst is provided, wherein the OER electrocatalyst is prepared using the preparation method described above.

[0017] As a preferred technical solution, the OER electrocatalyst, wherein the OER electrocatalyst has a current density of 50 mA cm in the OER reaction of 1.0 M KOH. -2 When the working potential of the OER electrocatalyst is 191 mV and the current density is 100 mA cm -2 The working potential of the OER electrocatalyst is 208 mV.

[0018] As a preferred technical solution, the OER electrocatalyst, wherein the OER electrocatalyst has a current density of 100 mA cm -2 The stable working time shall not be less than 100h.

[0019] Beneficial effects: Compared with the prior art, the present invention adopts reconstruction engineering and heterogeneous interface engineering to make the prepared OER electrocatalyst have excellent OER catalytic activity in an alkaline environment. In the OER reaction, under 1.0M KOH electrolyte, the OER electrocatalyst only needs 191mV and 208mV overpotentials to reach 50mA cm -2 and 100mA cm -2 At the same time, the OER electrocatalyst can be -2 It can work stably for more than 100 hours under high current density conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the synthesis of the Fe3S4 / Ni(OH)2 catalyst provided by the present invention;

[0021] Figure 2 are electron microscope images, where a is the SEM image of Fe / Ni precursor, b is the SEM image of Fe3S4 / Ni(OH)2 / NF, c is the TEM image of Fe3S4 / Ni(OH)2 / NF, d is the HR-TEM image of Fe3S4 / Ni(OH)2 / NF, e is the SEAD image of Fe3S4 / Ni(OH)2 / NF, f is the HAADF-STEM image of Fe3S4 / Ni(OH)2 / NF (with energy dispersion spectrum embedded), and gj is the Ni, Fe, S, and O element mapping images of Fe3S4 / Ni(OH)2 / NF;

[0022] Figure 3 is the OER performance test of the catalyst: where a is the double layer capacitance, b is the Faraday efficiency of the OER process, and c is the current density of 10 mA cm -2 d is the catalyst chronoamperometry curve, d is the comparison chart of different catalyst properties;

[0023] Figure 4 a is the SEM image of Fe3S4 / Ni(OH)2 / NF after OER reaction, and b is the HR-TEM image of Fe3S4 / Ni(OH)2 / NF after OER reaction;

[0024] Figure 5 XPS spectra of catalysts such as Co3S4 / Ni3S2 / NF, Co3S4 / NF and Ni3S2 / NF: a is the full XPS spectrum, b is Co 2p, c is Ni 2p, and d is S2p;

[0025] Figure 6 UPS spectra of Ni(OH)2 / NF, Fe3S4 / NF and Fe3S4 / Ni(OH)2 / NF catalysts. DETAILED DESCRIPTION

[0026] The present invention provides an OER electrocatalyst and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0027] It will be understood by those skilled in the art that, unless otherwise stated, the singular forms "a", "an", "said" and "the" used herein may also include plural forms. It should be further understood that the term "comprising" used in the specification of the present application refers to the presence of the features, integers, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations. It should be understood that the term "and / or" used herein includes all or any unit and all combinations of one or more associated listed items.

[0028] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with those in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as here.

[0029] It should be understood that the sequence number and size of each step in this embodiment do not mean the order of execution, and the execution order of each process is determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiment of this application. All instruments used are commercially available products.

[0030] Combination Figure 1 The method for preparing the OER electrocatalyst provided by the present invention comprises:

[0031] Step 10: Add iron salt, nickel salt, nitrogen source and nickel foam substrate into water to obtain a mixed solution, wherein the water can be deionized water or distilled water.

[0032] In the present invention, nickel foam (NF) needs to be pretreated before use. The nickel foam can be placed in a hydrochloric acid solution for ultrasonic treatment, placed in anhydrous ethanol for ultrasonic treatment again, and then washed with deionized water. After drying, a clean NF is obtained. Iron salts include but are not limited to ferric nitrate nonahydrate and ferric sulfate heptahydrate; nickel salts include but are not limited to nickel chloride and nickel nitrate hexahydrate; nitrogen sources include but are not limited to urea, ammonium fluoride, ammonium sulfate and ammonium nitrate. The molar ratio of iron salt, nickel salt and nitrogen source can be 1:5:35. At this ratio, the prepared precursor has a good nano-morphology.

[0033] Step 20: reacting the mixed solution under a preset temperature condition to obtain a precursor.

[0034] In the present invention, the mixed solution prepared in step S10 is transferred to a reactor, the reactor is heated to 100-140° C., and kept at this temperature for 2-10 hours. After the reaction is completed, a precursor, such as a Fe / Ni precursor, is obtained. The obtained precursor is washed with deionized water and anhydrous ethanol, respectively, and then dried to obtain a Fe / Ni precursor with impurities removed.

[0035] Step 30: sulfurize the precursor to obtain the OER electrocatalyst.

[0036] In the present invention, the Fe / Ni precursor from which impurities have been removed can be placed on the left side of the porcelain boat, and sulfur powder can be placed on the right side of the porcelain boat (or vice versa). The porcelain boat is placed in a tubular furnace and heated in a nitrogen atmosphere. After the temperature reaches a preset temperature, it is kept at this temperature for 2 hours for high-temperature sulfurization reaction to obtain the final product and mark it as Fe3S4 / Ni(OH)2 / NF. High-temperature sulfurization in a tubular furnace can convert the precursor into a sulfide. The introduction and modification of sulfur atoms stabilizes oxygen vacancies, forms a coordination of metal and sulfur, and effectively adjusts the electronic structure of the active site.

[0037] Based on the same inventive concept, the present invention also provides an OER electrocatalyst, which is prepared by the above-mentioned preparation method. The specific preparation method has been explained above and will not be repeated here.

[0038] The above technical solution provided by the present invention is further explained below through a specific preparation method.

[0039] Example 1

[0040] Synthesis of Fe3S4 / Ni(OH)2 / NF using nickel foam as substrate

[0041] Pretreatment of nickel foam (NF) substrate: A 2 cm × 3 cm × 1.5 mm NF sheet was ultrasonicated in 3M hydrochloric acid solution for 30 min, ultrasonicated in anhydrous ethanol for 20 min, and ultrasonicated in deionized water for 20 min, then washed three times with deionized water, and finally dried in a vacuum oven at 60 ° C for 3 h to obtain a clean NF.

[0042] 0.2 mmol ferric nitrate nonahydrate, 1 mmol nickel chloride, 2 mmol ammonium fluoride and 5 mmol urea were dispersed in 20 mL deionized water and stirred at room temperature (24°C) for 1 hour to obtain a solution. The solution and the treated NF were transferred to a 20 mL reactor and reacted at 120°C in a constant temperature oven for 6 hours. The obtained product was marked as Fe / Ni percursor. After the reaction was completed, the above product was rinsed with deionized water and anhydrous ethanol three times each and dried at 75°C for 10 hours.

[0043] The precursor obtained above was placed on the left side of the porcelain boat, and 0.1 g of sulfur powder was placed on the right side of the porcelain boat. The porcelain boat was placed in a tube furnace. Under a nitrogen atmosphere, the starting temperature was 20 °C and the heating rate was 3 °C min -1 When the temperature reached 350°C, the temperature was kept at this temperature for 2 h for high-temperature sulfurization reaction to obtain the final product and mark it as Fe3S4 / Ni(OH)2 / NF.

[0044] Comparative Example 1

[0045] Synthesis of Ni(OH)2 / NF

[0046] Pretreatment of nickel foam (NF) substrate: A 2 cm × 3 cm × 1.5 mm NF sheet was ultrasonicated in 3M hydrochloric acid solution for 30 min, ultrasonicated in anhydrous ethanol for 20 min, and ultrasonicated in deionized water for 20 min, then washed three times with deionized water, and finally dried in a vacuum oven at 60 ° C for 3 h to obtain a clean NF.

[0047] Disperse 1 mmol nickel chloride, 2 mmol ammonium fluoride and 5 mmol urea in 20 mL deionized water, stir at room temperature for 1 hour to dissolve, and obtain a solution. Transfer the solution and the treated NF to a 20 mL reactor, and react at 120 ° C in a constant temperature oven for 6 hours. The obtained product is marked as Ni (OH) 2 / NF. After the reaction is completed, the powder sample is collected after centrifugal washing with deionized water and ethanol for several times, and dried at 70 ° C for 5 hours to obtain Ni (OH) 2 / NF.

[0048] Comparative Example 2

[0049] Synthesis of Fe3S4 / NF

[0050] Pretreatment of nickel foam (NF) substrate: A 2 cm × 3 cm × 1.5 mm NF sheet was ultrasonicated in 3M hydrochloric acid solution for 30 min, ultrasonicated in anhydrous ethanol for 20 min, and ultrasonicated in deionized water for 20 min, then washed three times with deionized water, and finally dried in a vacuum oven at 60 ° C for 3 h to obtain a clean NF.

[0051] Disperse 1 mmol of ferric nitrate nonahydrate, 2 mmol of ammonium fluoride and 5 mmol of urea in 20 mL of deionized water and stir at room temperature for 1 hour to dissolve. Transfer the solution and the treated NF to a 20 mL reactor and react at 130°C in a constant temperature oven for 6 hours. The obtained product is marked as Fe / NF. After the reaction is completed, rinse the above product with deionized water and anhydrous ethanol three times each and dry it at 75°C for 10 hours.

[0052] The precursor obtained above was placed on the left side of the porcelain boat, and 0.1 g of sulfur powder was placed on the right side. The porcelain boat was placed in a tube furnace. Under a nitrogen atmosphere, the starting temperature was 20 °C and the heating rate was 3 °C min -1 When the temperature reaches 350°C, the temperature is kept at this temperature for 2 hours for high-temperature sulfurization reaction to obtain the final product and mark it as Fe3S4 / NF.

[0053] The products obtained in Example 1 and Comparative Examples 1 and 2 were tested, and the results were as follows: Figure 2 As shown, a shows the SEM image of Fe / Ni percursor. The precursor is in the shape of nanoflowers. After high-temperature sulfurization, the Fe3S4 / Ni(OH)2 / NF catalyst still retains the nanoflower morphology intact (b), and its nanosheet surface is smooth. c is the TEM image of Fe3S4 / Ni(OH)2 / NF catalyst. According to the high-resolution transmission electron microscopy (HR-TEM) image, the crystal plane spacing of 0.26nm corresponds to the (110) crystal plane of Ni(OH)2, and the crystal plane spacing of 0.25nm corresponds to the (400) crystal plane of Fe3S4 (d). The test results show that the catalyst is composed of two phases of Fe3S4 and Ni(OH)2, and a heterogeneous structure material catalyst is successfully prepared. The electron diffraction pattern of the catalyst also further verifies this conclusion. e shows the (200) crystal plane corresponding to Ni(OH)2, and the (551) and (711) crystal planes corresponding to Fe3S4. The EDX energy spectrum shows that the content ratio of Fe to Ni elements is 1:5 ( Figure 2 In addition, the energy dispersive X-ray spectrum shows that Ni and O are evenly distributed in the catalyst, while Fe and S are mainly distributed in the center of the catalyst and less distributed at the edge (e.g. Figure 2 (as shown in gj in ).

[0054] Electrocatalytic performance of Fe3S4 / Ni(OH)2 / NF electrocatalyst

[0055] The OER catalytic activity of the prepared Fe3S4 / Ni(OH)2 / NF catalyst in alkaline conditions (1.0 M KOH solution) was studied using a three-electrode system. -2 At current densities of 1.3, 1.5, and 2.0, the overpotentials required for the Fe3S4 / Ni(OH)2 / NF catalyst were 191, 208, and 280 mV, respectively, indicating that the coupling between the heterogeneous structures greatly increased the charge transfer rate and significantly optimized the OER performance of the catalyst. At the same time, the Tafe l slope of the Fe3S4 / Ni(OH)2 / NF catalyst was 24.2 mVdec -1 , lower than Fe3S4 / NF (41.9mV dec -1)、Ni(OH)2 / NF(123.9mV dec -1 ) and RuO2 / NF (140.2mV dec -1 ), indicating that the OER kinetics of Fe3S4 / Ni(OH)2 / NF catalyst is the fastest. Fe3S4 / Ni(OH)2 / NF catalyst has the smallest charge transfer resistance, which demonstrates the excellent interfacial charge transfer kinetics of this catalyst.

[0056] The electrochemical double layer capacitance (C dl ) to evaluate the electrochemically active surface area (ECSA) ( Figure 3 The larger ECSA means more active sites are exposed. -1 ) to perform CV cycle test, and then fit the C dl The value is used to evaluate the electrochemically active surface area of ​​the catalyst. Figure 3 As can be seen in a, compared with Fe3S4 / NF (7.1mF cm -2 ) and Ni(OH)2 / NF(3.2mF cm -2 ), Fe3S4 / Ni(OH)2 / NF has the largest electrochemical active area (17.4 mF cm -2 ), indicating that more active sites are exposed in Fe3S4 / Ni(OH)2 / NF. Figure 3 In Figure b, the Faradaic efficiency of the Fe3S4 / Ni(OH)2 / NF catalyst was calculated to be 98.64%.

[0057] The stability of the catalyst is characterized by measuring the IT curve of the sample. Figure 3 As shown in c, at 100mA cm -2 Under a constant current density of , Fe3S4 / Ni(OH)2 / NF can work stably for 100 hours with a loss of only 8%, indicating that the Fe3S4 / Ni(OH)2 / NF catalyst still has excellent long-term stability at high current density, which is significantly improved compared with the stability of other nickel-based sulfides.

[0058] At the same time Figure 3 As shown, the Fe3S4 / Ni(OH)2 / NF catalyst exhibits excellent activity at high current density compared with the existing Ni-Fe-based catalysts.

[0059] Furthermore, the morphology, surface composition and element valence state of Fe3S4 / Ni(OH)2 / NF after OER test were systematically characterized by SEM, HRTEM and XPS. Figure 4 Figure a is a SEM image of Fe3S4 / Ni(OH)2 / NF after OER test. It can be found that the morphology of Fe3S4 / Ni(OH)2 / NF has changed significantly. The originally smooth nano-petals have turned into foam, but the overall shape remains spherical, indicating that the catalyst surface has been reconstructed during the OER process. It can be observed in the HR-TEM image that the lattice fringe spacing of 0.26nm belongs to the (012) crystal plane of Ni(OH)2, while the lattice fringe spacing of 0.22nm belongs to the (402) crystal plane of FeO(OH) Figure 4 (b) Ni(OH)2 still exists, while the Fe3S4 phase is reconstructed during the reaction and transformed into Fe oxyhydroxide in situ, with S leaching out, which can further explain the changes in morphology.

[0060] Going a step further, Figure 5 As shown in Figure 2, the surface element composition and valence state of the catalyst were further analyzed by X-ray photoelectron spectroscopy (XPS). In the Ni 2p spectrum, the characteristic peaks at 856.5 eV and 874.1 eV can be attributed to Ni 2+ Compared with the single Ni(OH)2 without heterogeneous structure, the Fe3S4 / Ni(OH)2 / NF catalyst Ni 2+ The characteristic peaks of are all shifted to the positive direction by 0.5 eV. Figure 5 b, it can be observed in the Fe 2p spectrum that the fitted peaks at 709.5 eV and 719.1 eV correspond to Fe 2+ , while the fitted peaks at 711.5 eV and 724.5 eV correspond to Fe 3+ , and compared with the single Fe3S4 phase, there is a 0.5 eV positive shift. 2+ and Fe 3+ The peak area of ​​the Fe3S4 / NF catalyst is larger than that of the Fe3S4 / NF catalyst. The higher binding energy and the larger peak area ratio can indicate that the charge transfer phenomenon in the heterogeneous structure changes the surface charge distribution of the single phase, making some Fe 3+ Reduced to Fe 2+ The shift in the peak position indicates that there is a strong electronic interaction between the two-phase heterostructure, which greatly promotes the charge transfer.

[0061] The characteristic peaks at 164.3eV and 163.1eV in the S2p spectrum are attributed to 2p1 / 2 and 2p3 / 2. Compared with the single phase, these two peaks move to higher binding energy, with a positive shift of about 0.5eV. At the same time, due to the heterogeneous structure, the peak area of ​​the scan is smaller than that of the single phase ( Figure 5 c) Combined Figure 5 It can be confirmed that the two characteristic peaks fitted at 531.3eV and 532.3eV in the O 1s spectrum can be attributed to the M-OH bond and the water molecules adsorbed on the surface, while the peak at the binding energy of 530.2eV is the MO bond. The change in binding energy brought about by the heterogeneous structure proves that the coupling between different phases can optimize the electronic environment of the metal center, adjust the microvalence state of the active site, further improve the catalyst performance, promote the reaction process in the direction of low energy barrier, and promote efficient OER reaction.

[0062] In addition, the ultraviolet emission spectroscopy (UPS) test ( Figure 6 ) The d-band centers of Fe3S4 / Ni(OH)2 / NF, Ni(OH)2 / NF, and Fe3S4 / NF catalysts can be obtained by calculation. The higher the d-band center position, that is, the closer it is to the Fermi level, the stronger the adsorption of the material to the intermediate. The d-band center of Fe3S4 / Ni(OH)2 / NF is calculated to be -4.80eV, which is closer to the Fermi level than Fe3S4 / NF (-5.04eV) and Ni(OH)2 / NF (-5.49eV), indicating that the formation of the heterostructure enhances the charge transfer effect and reduces the required adsorption energy, making it easier for the active sites to adsorb and capture reactive free radicals, reducing the reaction energy barrier and efficiently promoting the OER reaction.

[0063] In summary, the present invention provides an OER electrocatalyst and a preparation method thereof, the preparation method comprising: adding an iron salt, a nickel salt, a nitrogen source and a nickel foam substrate to water to obtain a mixed solution; reacting the mixed solution under a preset temperature condition to obtain a precursor; and subjecting the precursor to a sulfurization treatment to obtain the OER electrocatalyst. In the present invention, the precursor of the nanoflower morphology formed in the hydrothermal process still retains the morphological characteristics of the nanoflower in the high-temperature sulfurization process, which allows sufficient active sites to be fully exposed. The heterogeneous interface of Fe3S4 / Ni(OH)2 has a synergistic effect, improves the charge distribution on the catalyst surface, accelerates the electron transfer rate, and effectively improves the OER catalytic activity (due to the difference in electronegativity between metal elements, the heterogeneous interface has a strong charge transfer effect, and the intact retention of the nanoflower morphology increases the surface area of ​​the catalyst, increases the higher exposure rate of the active sites, and improves the accessibility of the electrolyte in the catalytic process. At the same time, the metal hydroxide oxide generated by in-situ reconstruction in the OER reaction activates the new active sites of the catalyst, which significantly improves the OER catalytic activity). The Fe3S4 / Ni(OH)2 / NF catalyst exhibits excellent electrochemical performance, with a current density of 50 mA cm in the OER reaction in 1.0 M KOH. -2 When the working potential of Fe3S4 / Ni(OH)2 / NF is only 191mV, the current density is 100mA cm -2 The working potential of Fe3S4 / Ni(OH)2 / NF is only 208mV. In the stability test under high current density, Fe3S4 / Ni(OH)2 / NF catalyst also showed excellent long-term stability. -2 It can work stably for 100h.

[0064] The Fe3S4 / Ni(OH)2 / NF catalyst demonstrates that the simultaneous combination of reconstruction engineering and heterogeneous engineering functionalization strategies can significantly optimize the performance of the catalyst. This work provides a feasible approach for the development of efficient high-current electrocatalysts.

[0065] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing an OER electrocatalyst, characterized in that: include: Adding iron salt, nickel salt, nitrogen source and nickel foam substrate into water to obtain a mixed solution; The mixed solution is reacted under a preset temperature condition to obtain a precursor; Placing the precursor in a reaction container, and placing sulfur powder on one side of the precursor; The reaction container is placed in a baking device and heated in an inert atmosphere to obtain the OER electrocatalyst; wherein the heating rate is 2-4°C min -1 ; Heating temperature is 300-400℃; The molar ratio of the iron salt to the nickel salt is 1:

5.

2. The method for preparing an OER electrocatalyst according to claim 1, characterized in that: The iron salt is ferric nitrate nonahydrate or ferric sulfate heptahydrate; the nickel salt is nickel chloride or nickel nitrate hexahydrate; and the nitrogen source is selected from one or more of urea, ammonium fluoride, ammonium sulfate and ammonium nitrate.

3. The method for preparing an OER electrocatalyst according to claim 1, characterized in that: The reaction is carried out under a preset temperature condition, wherein the preset temperature is 100-140° C. and the reaction time is 2-10 hours.

4. An OER electrocatalyst, characterized in that The OER electrocatalyst is prepared by the preparation method described in any one of claims 1-3.

5. The OER electrocatalyst according to claim 4, characterized in that The OER electrocatalyst has a current density of 50 mA cm in the OER reaction in 1.0 M KOH. -2 When the working potential of the OER electrocatalyst is 191 mV and the current density is 100 mA cm -2 The working potential of the OER electrocatalyst is 208 mV.

6. The OER electrocatalyst according to claim 4, characterized in that The OER electrocatalyst has a current density of 100 mA cm -2 The stable working time shall not be less than 100h.

Citation Information

Patent Citations

  • Low-cost catalytic electrode applied to seawater rapid full-electrolysis hydrogen production, preparation and application

    CN115505961A

  • Method for improving electrocatalytic stability of nickel-based sulfide catalyst in oxygen evolution reaction

    CN116623225A

  • AEMWE cathode electrode material under large current density and macro preparation method and application thereof

    CN118480811A